Abnormal Decrease of Macrophage ALKBH5 Expression Causes Abnormal Polarization and Inhibits Osteoblast Differentiation - Junquan Weng; Haidong Fan; Huijuan Liu; Su Tang; Yuyan Zheng (Stem Cells International)
Peri-implant tissue inflammation is an inflammatory injury that occurs in the soft and hard tissues surrounding the implant and is the main cause of short- or long-term failure of implant prosthetic restorations, which is compounded by bone loss and bone destruction in the alveolar bone of diabetes patients with peri-implantitis. However, the mechanisms underlying the persistence of diabetic peri-implantitis, as well as the essential connections and key molecules that regulate its start and progression, remain unknown. In this study, we discovered that M1 macrophage polarization was abnormally enhanced in diabetic peri-implantitis and influenced the osteogenic differentiation of mesenchymal stem cells. RNA sequencing revealed that ALKBH5 expression was abnormally reduced in diabetic peri-implantitis. Further mechanism study showed that ALKBH5 and its mediated m6A can influence osteogenic differentiation, which in turn influences the persistence of diabetic peri-implantitis. Our findings present a new mechanism for the suppression of osteoblast development in diabetic peri-implantitis and a new treatment strategy to promote anabolism by inhibiting ALKBH5.